HUBUNGAN INTERAKSI SOSIAL DAN TINGKAT KEMANDIRIAN DENGAN KUALITAS HIDUP LANSIA DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM - Raja Gukguk, Damian; Gemini, Savitri; Erda, Roza (Ensiklopedia of Journal, 2025)
The elderly population continues to increase. The increase in the number of elderly population is accompanied by various health problems faced by the elderly.Changes indecreasing abilities in the elderly cause a decline in physical condition,level of independence, social and psychological. One of the impacts of social changes experienced by the elderly is withdrawal. from the environment the elderly live in. Changes in physical decline cause limited independence which causes the elderly's ability to fulfill their life to be limited and dependent on other people and has an impact on the quality of life of the elderly. The aim of this research is to determine the relationship between social interaction and the level of independence and the quality of life of the elderly. This research is an analytical research with a cross sectional design. The sampling technique was purposive sampling with a sample size of 66 respondents. The data collection method used a questionnaire sheet. The research results showed that there was a relationship between social interaction and the level of independence and quality of life which was significant with a p value <0.005. It is hoped that the results of this research can increase knowledge for the elderly and researchers. To improve the quality of life of the elderly, it is hoped that they will be more productive again by increasing the creativity of handicrafts to increase the elderly's income and for the welfare of the elderly's lives.Kata Kunci: Quality Of Life, Social Interaction, Level Of Independence, Elderly